A missed opportunity to save a cultural district? The post-pandemic aftermath at Bairro Alto, Lisboa - Costa, P. (ACEI 2023 Conference - 22nd International Conference on Cultural Economics: “Cultural Economics, Coming Together: Bridging Distances, Crossing Boundaries”, 2023)
In several previous works and research projects along the last two decades we had the opportunity to discuss the evolution of the Bairro Alto neighborhood (and its surrounding areas) in Lisbon, Portugal, as a cultural district, as well as to study the central factors for the resilience and sustainability of creative dynamics in this area of the city. As in several other neighborhoods with similar characteristics around the world, its evolution over the last decades has been marked by profound transformations and the decline of much of the cultural activities and creative dynamics that characterized it, asphyxiated in the face of the processes of massification, gentrification and turistification of the area, which gradually lost the various central functions in a creative neighborhood. Against the background of the development of cognitive-cultural capitalism and the processes of global financialization, with particular weight in the local real estate market in recent decades, the entire historic center of Lisbon has seen profound demographic, social, economic and cultural transformations, which naturally have also profoundly marked this particular neighborhood as well as the creative dynamics throughout the city. At the same time the erratic and often little focused nature of planning and public policies on this area, as well as on the entire historical center of the city, has allowed and even promoted the advancement of these dynamics. The profound social, economic and cultural transformations associated with the health crisis of COVID-19 and the post-pandemic period were seen as a unique opportunity to rethink the downward trajectory of this neighborhood and to consider the possibility of its revitalization as a creative center in the city. However, the recent experience have been pointed in a different direction, and the pandemic aftermath have been revealing a repetition and even an increase of the mistakes and errors that have been conducting and feeding the downward trajectory of this neighborhood as creative area in the city of Lisbon. Based on a set of interviews with residents and local stakeholders, this text presents a reflection on the (unrealized) potential of transformations associated with the COVID-19 pandemic period and the post-pandemic evolution for the revitalization of this area of the city, enquiring the role of the various agents and, in particular, of the public authorities in promoting a more resilient and sustainable solution for the development of this area of the city.